2008
DOI: 10.1111/j.1600-0668.2008.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of interventions to improve ventilation behavior in primary schools

Abstract: To improve ventilation behavior and indoor air quality in schools, CO(2) warning device and teaching package combined with a class-specific ventilation advice, are effective tools, while giving the ventilation advice solely, is not effective. Although ventilation is significantly improved through behavioral change, the ventilation rate is still insufficient to maintain good air quality during the full school day. Therefore, the improvement of the ventilation facilities is recommended. Hence, until ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…Based on CO 2 levels, inadequate ventilation appears to be a common IAQ problem encountered in the studied classrooms, reinforcing earlier studies (Geelen et al., ; Madureira et al., ; Mumovic et al., ; Pegas et al., ). Based on a 1000 ppm CO 2 limit (ASHRAE 62‐2001, 2001) and using school‐day averages, 86% of the classrooms were inadequately ventilated.…”
Section: Discussionsupporting
confidence: 83%
“…Based on CO 2 levels, inadequate ventilation appears to be a common IAQ problem encountered in the studied classrooms, reinforcing earlier studies (Geelen et al., ; Madureira et al., ; Mumovic et al., ; Pegas et al., ). Based on a 1000 ppm CO 2 limit (ASHRAE 62‐2001, 2001) and using school‐day averages, 86% of the classrooms were inadequately ventilated.…”
Section: Discussionsupporting
confidence: 83%
“…Based on CO 2 levels, inadequate ventilation appears to be a common IAQ problem encountered in the studied classrooms, reinforcing earlier studies [4,18,20,47,48]. Based on a 1000 ppm CO 2 limit [46] and using school-day averages, 86% of the classrooms were inadequately ventilated.…”
Section: Levels and Source Apportionment Of Co 2 Pm 10 And Vocssupporting
confidence: 67%
“…Several studies have monitored indoor air concentrations of gaseous compounds (Stranger et al, 2007), particles (Branis et al, 2005;Fromme et al, 2007Fromme et al, , 2008Tran et al, 2012Tran et al, , 2014, semi-volatile organic compounds (Lim et al, 2014;Wu et al, 2010), and allergens (Salo et al, 2009). Other studies have investigated outdoor air contributions Blondeau et al, 2005;Madureira et al, 2012), the role of different ventilation strategies (Geelen et al, 2008;Guo et al, 2008;Rosbach et al, 2013;Santamouris et al, 2008) and the relationships with student health (Daisey et al, 2003;Mendell et al, 2013;Simoni et al, 2011) and performance (Bak o-Bir o et al, 2012;Haverinen-Shaughnessy et al, 2011;Shendell et al, 2004;Twardella et al, 2012;Wargocki and Wyon, 2007). Few studies have reported correlations between ventilation and IAQ in schools.…”
Section: Introductionmentioning
confidence: 99%